2022
DOI: 10.1167/tvst.11.6.17
|View full text |Cite
|
Sign up to set email alerts
|

Sema3A Antibody BI-X Prevents Cell Permeability and Cytoskeletal Collapse in HRMECs and Increases Tip Cell Density in Mouse Oxygen-Induced Retinopathy

Abstract: Purpose Semaphorin 3A (Sema3A) is an axonal guidance molecule that inhibits angiogenesis by vasorepulsion and blocks revascularization in the ischemic retina. BI-X is an intravitreal anti-Sema3A agent under clinical investigation in patients with proliferative diabetic retinopathy (PDR) and diabetic macular ischemia (DMI). Methods Surface plasmon resonance was used to determine binding affinity of BI-X to human and murine Sema3A. In vitro, human retinal microvascular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This conjecture is supported by our finding that, when compared with aflibercept, intravitreal administration of BI-Y into the eye of mice with OIR significantly reduces the size of the avascular area and significantly increases tip cell density at the avascular front. These results align with previous work demonstrating the central role of Sema3A and Nrp-1 in angiogenesis and endothelial leakage using mouse models (Fantin et al, 2014, Fernández-Robredo et al, 2017, Nakamura et al, 2022, Zippel et al, 2022.…”
Section: Bi-y Does Not Affect Vegf-a-dependent Laser-induced Choroidalsupporting
confidence: 92%
See 1 more Smart Citation
“…This conjecture is supported by our finding that, when compared with aflibercept, intravitreal administration of BI-Y into the eye of mice with OIR significantly reduces the size of the avascular area and significantly increases tip cell density at the avascular front. These results align with previous work demonstrating the central role of Sema3A and Nrp-1 in angiogenesis and endothelial leakage using mouse models (Fantin et al, 2014, Fernández-Robredo et al, 2017, Nakamura et al, 2022, Zippel et al, 2022.…”
Section: Bi-y Does Not Affect Vegf-a-dependent Laser-induced Choroidalsupporting
confidence: 92%
“…expression, and Zippel et al showed that application of a Sema3A neutralizing antibody (referred to as BI-X) in an OIR resulted in a significant negative correlation between tip cell density and size of the avascular area and a trend for reduction of the avascular area (Nakamura et al, 2022, Zippel et al, 2022; i.e. the effects of the two antibodies are qualitatively similar.…”
Section: Nakamura Et Al Found That Induction Of Vein Occlusion Signif...mentioning
confidence: 99%
“…Silencing expression of Sema3A in a mouse model of oxygen-induced retinopathy has been shown to maintain neuroretinal function [33]. Furthermore, recent data show that administration of the anti-Sema3A agent BI 764524 in a mouse model of oxygen-induced retinopathy significantly reduces avascular area size [27] and had a beneficial effect on intraretinal oedema and ischaemia in a retinal vein occlusion mouse model [34]. This suggests that Sema3A plays a targetable and pathological role in retinal ischaemia by contributing to vascular and subsequently neuronal damage, ultimately resulting in progressive vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…BI 764524 is an intravitreal anti-Sema3A ischaemia modulator agent. Preclinical data show that BI 764524 reduces the area of ischaemia in mouse retinas with oxygen-induced retinopathy [27]. HORNBILL is the first clinical trial assessing a treatment for DMI and the first trial to use OCTA as a means to define and examine DMI.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Sema6A inhibits the formation of endothelial cells. Consequently, when the expression of sema6A in the retina or vitreous decreases, the production and number of new endothelial cells increases, thereby increasing their content in the vitreous and decreasing the clarity of the vitreous [ 103 , 104 ] (Nina et al, 2022; Guo et al, 2019).…”
Section: Application Of Proteomics In Optic Nerve Injury Diseasesmentioning
confidence: 99%